2012
DOI: 10.1108/10662241211235680
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to the analysis of online profiles

Abstract: Purpose -The article aims to present a holistic approach to analysis of patterns on complex online profiles, demonstrated on profiles of European scientists. Design/methodology/approach -An existing analytical framework was developed to incorporate a holistic understanding of online profiles. The framework was applied to a sample of 188 online profiles belonging to 48 European scientists. The profile data were studied on three levels (content-unit level, profile-instance level, and profile-network level), usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Such a combination of authorships is most evident on the commercial platforms, where the platforms invite others to contribute and make use of algorithms to form the researcher profile. Although the level of other-and system-writing of the academic self differed between the institutional web sites and the commercial platform profiles included in the study, the platforms were primarily used as tools for visibility, as shown by Bukvova (2012). There was fairly little indication of differences that originate in the commercial platforms being used for networking, an affordance which is less pronounced on institutional web sites.…”
Section: Co-construction Of Self-making In Academic Web Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a combination of authorships is most evident on the commercial platforms, where the platforms invite others to contribute and make use of algorithms to form the researcher profile. Although the level of other-and system-writing of the academic self differed between the institutional web sites and the commercial platform profiles included in the study, the platforms were primarily used as tools for visibility, as shown by Bukvova (2012). There was fairly little indication of differences that originate in the commercial platforms being used for networking, an affordance which is less pronounced on institutional web sites.…”
Section: Co-construction Of Self-making In Academic Web Profilesmentioning
confidence: 99%
“…A few studies of academic web profiles or researcher web presence have looked into what characterizes the profiles. Bukvova (2012) found the most common type of content on both institutional web sites and social network sites to be what she terms "visit card, curriculum vitae", but common were also "visit card, personal identification". Both were mainly oriented towards factual information.…”
Section: Features Of Academic Web Profilesmentioning
confidence: 99%
“…Self-expression can be a process by which people attempt to control the impressions others have of them [52]. Bukvova [53], focusing on the online profiles of European scientists, suggested that Internet presence should be treated as an important strategic instrument for self-presentation because it can be an effective tool for communication with peers, as well as with other stakeholders. Since the Internet offers opportunities for personalized self-presentation according to individual needs [53], online users are likely to user UGC as a communication channel to reveal themselves.…”
Section: Self-expression Motivementioning
confidence: 99%
“…The academic networking project sought to examine in detail the structure of academics' ego-networks on two contrasting social media platforms which they use in relation to their professional work, and to understand the significance of those structures through interviews with participants. Academic SNS and Twitter were selected as contrasting platforms because while academic SNS are designed for a specifically academic audience, academics often view them as an online CV, while more actively discussing their work on Twitter (Bukvova, 2012;Van Noorden, 2014).…”
Section: Research Contextmentioning
confidence: 99%